2006
DOI: 10.1007/s11745-006-5077-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the α‐tocopherol transfer protein in mice: Lack of response to dietary vitamin E or oxidative stress

Abstract: The alpha-tocopherol transfer protein (TTP) plays an important role in the regulation of plasma alpha-tocopherol concentrations. We hypothesized that hepatic TTP levels would be modulated by dietary vitamin E supplementation and/or by oxidative stress. Mice were fed either a High E (1150 mg RRR-alpha-tocopheryl acetate/kg diet) or a Low E (11.5 mg/kg diet) diet for 2 wk. High E increased plasma and liver alpha-tocopherol concentrations approximately 8- and 40-fold, respectively, compared with Low E-fed mice, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
1
24
0
Order By: Relevance
“…The most abundant isoforms are a-tocopherol and g-tocopherol, which differ by one methyl group ( Figure 1A). There are approximately 10-fold higher tissue concentrations of a-tocopherol than g-tocopherol due to preferential transfer of a-tocopherol in the liver by a-tocopherol transfer protein and due to a higher rate of production of g-tocopherol metabolites for excretion (10,11). The plasma levels of tocopherols correlate with lung tissue levels of tocopherols in humans and mice (7,8,12).…”
mentioning
confidence: 99%
“…The most abundant isoforms are a-tocopherol and g-tocopherol, which differ by one methyl group ( Figure 1A). There are approximately 10-fold higher tissue concentrations of a-tocopherol than g-tocopherol due to preferential transfer of a-tocopherol in the liver by a-tocopherol transfer protein and due to a higher rate of production of g-tocopherol metabolites for excretion (10,11). The plasma levels of tocopherols correlate with lung tissue levels of tocopherols in humans and mice (7,8,12).…”
mentioning
confidence: 99%
“…Moreover, a-TTP expression is reduced in the liver of methioninecholine deficiency (MCD) rats, which are known as a model of non-alcoholic fatty liver disease, and presents increased lipid peroxidation of the liver and hepatic dysfunction (33). Bella et al reported that exposure to environmental tobacco smoke does not alter hepatic expression (34). We have previously reported that hepatic a-TTP expression and plasma a-tocopherol levels were elevated in rat models with type 2 diabetes showing lipid peroxidation (5).…”
Section: Discussionmentioning
confidence: 83%
“…However, in the present study, hepatic α-TTP protein levels in both groups of rats fed the OFO diet were unchanged, although lipid peroxidation increased. Unchanged hepatic α-TTP protein levels are also observed in rats exposed to tobacco smoke [35], despite a lower α-tocopherol concentrationin lung and higher lipid peroxidation in the rat liver. The downregulation of α-TTP levels seen in galactosamineinduced liver injury [34] is an acute response (24-48 h), and, since the OFO diet was fed for a long time, α-TTP levels may have changed during the acute injury and restored subsequently.…”
Section: Discussionmentioning
confidence: 94%